UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI METODE SMALL GROUP DISCUSSION MATERI PECAHAN - Aprilestari, Amelia Dwi; Jamaludin, Ikbal; Munifah, Mumun; Prastiwigari, Rahajeng; Birsyada, Muhammad Iqbal; Warsito, W. (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
The purpose of this study was to determine the learning outcomes of students in mathematics subjects on the material of fraction story problems in the form of ordinary fractions and mixed fractions.The research method used was classroom action research. The study was conducted in class 5B SDIT Salsabila 3 Banguntapan by implementing the Small Group Discussion method. The study was conducted in two cycles through the stages: 1) planning, 2) implementation, 3) observation, and 4) reflection. In this study, the level of success was seen based on individual criteria and classical criteria.The results showed that the use of the Small Group Discussion method on the material of ordinary fraction story problems and mixed fractions can significantly improve student learning outcomes. In the pre-cycle, the learning outcome completion was only 21.74% with an average value of 59.86. In cycle I, although it had not reached the desired completion criteria (75%), the implementation in cycle II increased the learning outcome completion to 69.57% with an average value of 71.08. In Cycle II, the completion of students' learning outcomes reached 91.30% or met the established completion criteria. Thus, the application of the Small Group Discussion method has proven effective in improving students' learning outcomes in fraction material.